Experimental Thrombosis in Rabbits: Evidence that Alkaline Phosphatase Enhances the Thrombogenic Effect of the Injected Ellagic Acid - Iatridis, P. G; Ferguson, J. H (Thrombosis and Haemostasis, 1966)
Intravenous injection of ellagic acid plus alkaline phosphatase in rabbits, induces a thrombotic tendency, which correlates with a hypercoagulability of the blood revealed by thrombelastography. Either ellagic acid (which suboptimally activates Hageman factor) or alkaline phosphatase, separately, gave negative results concerning the incidence of thrombosis. This clearly indicates that alkaline phosphatase in vivo, as was previously shown in vitro, acts only in the presence of an active SF. The electrophoretic study of the distribution of alkaline phosphatase, in platelet-poor plasma samples secured from rabbits, with and without injection of an alkaline phosphatase preparation, suggests the probability that it is the alkaline phosphatase activity which is located in the “beta” fraction that contributes the responsible co-factor for the thrombogenesis.